Implementasi E-Module Interaktif Berbasis Historical Perspective Pada Mata Kuliah Jurnalisme Kepariwisataan Sejarah - Matitaputty, Jenny Koce; Hetharion, Bety Hetharion D. S.; Pattiasina, Johan; Ima, Wa; Pusparani, Rina; Far-Far, Gazali; SOPACUA, JEMS (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to determine the differences in learning outcomes before and after implementing an interactive e-module based on a historical perspective in the historical tourism journalism course for students in the 4th semester of History Education. It is hoped that through interactive e-module media, it is hoped that it will help make it easier for students as future history teachers to have more historical values, the importance of maintaining the existence of these historical sites as part of the evidence of Maluku's history that needs to be retold to each generation. This research uses a pre-experiment research type: One-Group Pretest-Posttest Design. It is hoped that this research will be able to increase students' historical awareness as well as increase historical knowledge about the stories behind every relic of the historical sites on Ambon Island, national and regional hero figures, and typical Maluku food. The subjects of this research are students of the 4th semester history education study program which offers the History learning Journalism course. The research results are based on the Paired Sample T-Test hypothesis test that there is a positive influence on the use of e-modules and an increase in student learning outcomes. This means that the conclusion that the e-learning module used is suitable for improving student learning outcomes.